Computation of trunk equilibrium and stability in free flexion-extension movements at different velocities - Bazrgari, B.; Shirazi-Adl, A.; Trottier, M.; Mathieu, P. (Journal of Biomechanics, 2008)
Velocity of movement has been suggested as a risk factor for low-back disorders. The effect of changes in velocity during unconstrained flexion-extension movements on muscle activations, spinal loads, base reaction forces and system stability was computed. In vivo measurements of kinematics and ground reaction forces were initially carried out on young asymptomatic subjects. The collected kinematics of three subjects representing maximum, mean and minimum lumbar rotations were subsequently used in the kinematics-driven model to compute results during the entire movements at three different velocities.